The Effect of Utilizing an Instructional Software of the Tutorial Type on the Achievement of Jordanian Tenth Graders’ in Arabic Grammar - Tawalbeh, Mohammad (Jordan Journal of Educational Sciences, 2006)
This Study aimed at identifying the effect of utilizing a computerized tutorial program on the achievement of Jordanian Tenth Grader's in Arabic Grammar. The sample of the study consisted of (104) Male & Female Students from a private School in Amman. The results of the study revealed that there were statistically significant differences (α = 0.05) attributed to: method of teaching (in favor of the computerized tutorial program), achievement level (in favor of the high achievement level), interaction between method and gender, interaction between method and achievement level, and interaction between gender and achievement level. The findings also showed that there were neither statistically significant differences (α = 0.05) attributed to gender, nor to the interaction between method, gender, and achievement level. The practical significance (Eta2) showed that the relation between the achievement level & achievement was the strongest relation between the variables of the study. Conducting research about Blended Learning was the most important recommendation of the study.